Education, Racism, and the Pandemic: A Pedagogical-Critical Analysis for Latin America - Pons-Giralt, Maikel; Ulloa-Guerra, Oscar; Martínez-Sierra, Ricel; del Prado Morales, Mirtha; Ortega-Breña, Mariana (Latin American Perspectives, 2025)
The pandemic deepened social and educational inequality for Afro-descendants and indigenous people in Latin America and the Caribbean. A regional analytical overview with a focus on Brazil and on the social and educational challenges faced by these people and the epistemological, ontological, and pedagogical alternatives for the inclusion of racialized persons during the pandemic. The analysis points to the need for and the viabililty of exploring innovative pedagogical paths for promoting ethnic-racial inclusion and an antiracist form of education that responds to our contemporary context.
La pandemia profundiza las brechas de desigualdad social y educacional para afrodescendientes e indígenas en América Latina y Caribe. Un panorama analítico regional, con foco en Brasil, acerca de los desafíos sociales y educacionales que enfrentan afrodescendientes e indígenas identifica fundamentos y experiencias que durante la pandemia constituyen alternativas epistemológicas, ontológicas y pedagógicas para la inclusión de personas racializadas. El análisis permite corroborar que es necesario y posible explorar caminos pedagógicos innovadores en la promoción de la inclusión étnico-racial y de una educación antirracista que contesten el escenario contemporáneo.
Keywords: education; racism; inequalities; pandemic Latin America and the Caribbean; COVID-19 pandemic; Latin America and the Caribbean